The current induced mass transformation of Ag alloy wire bonded led chip - Xiaohong Yuan; Qinlian He; Shanju Zheng; Jiaheng Zhang; Dapeng Yang; Qinsong Bi; Yuxi Luo; Dengquan Chen; Xiaojing Wang (Journal of Materials Research and Technology)
The high input and output (I/O) data exchange, coupled with continuous increase in power density, elevates the risk of bonding interface performance degradation and electromigration (EM) failure during electrical transmission. This leads to polarity differences in interconnection structure, underscoring the urgent need to clarify the evolution of microscale bonding interfaces. This study investigates polarity effect in the chip-side Ag/Al system, revealing the evolution process of bonding interface under high current density. An EM theoretical model is established to analyze current-induced polarity effect on material migration and the growth evolution of intermetallic compounds (IMC) at the interface. Specifically, the cathode IMC layer thickness increased from 2.6 μm to 7.5 μm with an increase rate of 188.46%. And the anode has a higher rate of 3.8% than the cathode. Characterization has determined that IMC at bonding interface is predominantly the Ag2Al phase. The bonding wire surfaces in the middle and near the Al pad experience a combination of compressive stress and thermal migration, leading to the formation of white particles. Additionally, due to the bias voltage effect, white silver dendrites grow toward the anode joint on the chip's anode side under the influence of electrochemical migration (ECM). Tensile tests indicate that mechanical properties of the interface deteriorate after EM, and fracture mode transitions from neck fracture before EM to current forms of neck fracture and joint detachment. This study supplements and enhances the research framework of Ag/Al interface IMC at bonding joints, contributing to further development of reliable electronic packaging devices.